PEMBERDAYAAN EKONOMI BERKELANJUTAN MELALUI PROGRAM PENANAMAN 10.000 BIBIT POHON DI DESA KALONG LIUD - Nirwana, Testa Pradia; Udiawati, Sherly Alfina; Maulana, Abdul Reza; Hasanah, Siti Zulfah; Hidayah; Gustiani, Dede Reni; Purba, Sean Fahlevi (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
The 10,000 tree planting program in Kalong Liud Village, Nanggung District, Bogor Regency, is a concrete step in integrating ecological aspects with the economic empowerment of rural communities. Reforestation activities maintain environmental balance while opening up sustainable social and economic opportunities. The types of trees planted include jackfruit, durian, soursop, guava, jengkol, mahogany, tabebuya, petai, and avocado, all of which have strategic value as food sources and local economic commodities. The results of the SWOT analysis confirmed that community support and soil fertility play a key role, while challenges arise from climate change and market price fluctuations. This program has also given rise to innovations in agricultural-based MSMEs, such as the production of dodol nangka, which increases product added value and creates new business opportunities. Thus, tree planting serves as a model for sustainable village development that integrates environmental conservation with community economic empowerment.